THE MODEL OF THE REFORMING HIGHER EDUCATION OF OUR COUNTRY - Sauch, P. (Continuing Professional Education: Theory and Practice, 2019)
It is offered the concrete steps of the reforming higher education of our country in the article; it is analyzed three types of the institutions of higher education; it is emphasized on the importance of the realization of the university‘s autonomy in the context of improving of the higher education. It is determined three objective factors, that are the incentives for the organization and development of higher education in Ukraine: 1) the increasing requirements for the qualification of human resources; 2) the transition of the industry to the smallscale production under the conditions of speedy changes of the models; 3) the increasing of the awareness of the selfworth quality of the university education as a personal and national heritage. These factors open the possibility of the development of two socially important directions of the higher education system‘s functioning: supplementary education of the certificated specialist and qualitative lifelong education. Modern education should be based on the processes that determine the image of the XXI century: globalization and ethnorenascence, informatization and formation of the world‘s culture, hard limitation of the mechanization and creation of the new technologies.